Carbon nanotube based polymer nanocomposites: biomimic preparation and organic dye adsorption applications1. Issue 100 (29th October 2015) - Xie, Yili; He, Chengbin; Liu, Leichun; Mao, Liucheng; Wang, Ke; Huang, Qiang; Liu, Meiying; Wan, Qing; Deng, Fengjie; Huang, Hongye; Zhang, Xiaoyong; Wei, Yen
<x xml:space="preserve">Abstract</x> Poly(sodium-p-styrene sulfonate) modified multi-walled carbon nanotubes (CNTs) have been prepared via a combination of mussel inspired chemistry and SET-LRP, and utilized for methylene blue removal with high efficiency.